2017
DOI: 10.1002/jhm.2670
|View full text |Cite
|
Sign up to set email alerts
|

Discharge Handoff Communication and Pediatric Readmissions

Abstract: BACKGROUND: Improvement in hospital transitional care has become a major national priority, although the impact on children's postdischarge outcomes is unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 35 publications
0
20
0
3
Order By: Relevance
“…The effect of PCIs on subsequent hospital use was evaluated in only 5 studies; in all of these studies, PCIs were pooled with other intervention types. 34,41,43,84,86 Only 2 of these studies revealed a significant effect on use. In their prospective cohort study, Cheney et al 34 found that combining a letter to the patient's primary care provider with CCIs and FEIs reduced readmissions (Table 2).…”
Section: Effects Of Provider Communication On Usementioning
confidence: 99%
See 3 more Smart Citations
“…The effect of PCIs on subsequent hospital use was evaluated in only 5 studies; in all of these studies, PCIs were pooled with other intervention types. 34,41,43,84,86 Only 2 of these studies revealed a significant effect on use. In their prospective cohort study, Cheney et al 34 found that combining a letter to the patient's primary care provider with CCIs and FEIs reduced readmissions (Table 2).…”
Section: Effects Of Provider Communication On Usementioning
confidence: 99%
“…The impact of PCIs was evaluated in only 5 studies. 34,41,43,84,86 Out of 59 studies in which CCIs were evaluated, postdischarge follow-up (via clinic, home visit, or telephone) was incorporated in 38, * and the impact of intensive discharge planning services was evaluated in 26. † Of 39 studies providing FEIs, ‡ inpatient parental education was incorporated in 29 studies (task-based or teachback learning was specifically noted in 2 of these studies), and 14 studies involved contingency planning in parental education.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Physician-scientists in general, and pediatric physicianscientists in particular, are vanishing. [1][2][3] Rates of National Institutes of Health (NIH) awards to pediatric departments have declined from 23.8% to 16.8% during the past 10 years. 4 Being granted an NIH independent investigator award (R01) is not only a means to support a physician-scientist's research but also is a commonly required milestone for promotion.…”
Section: Name and Characteristics Of National Institutes Of Health R0mentioning
confidence: 99%